Depletion of LncRNA NEAT1 Rescues Mitochondrial Dysfunction Through NEDD4L-Dependent PINK1 Degradation in Animal Models of Alzheimer’s Disease - Huang, Zhonghua; Zhao, Jing; Wang, Wei; Zhou, Jun; Zhang, Jie (Frontiers in Cellular Neuroscience, 2020)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder and the main cause of dementia among the elderly worldwide. Unfortunately, the mechanism of AD remains unclear, and no effective therapies are available as yet. Increasing studies demonstrated that the long noncoding RNAs (LncRNAs) played a notably role in the pathogenesis of plenty of human diseases, and served as biomarkers and potential therapeutic targets. However, the function of LncRNAs in AD remains unclear. This study aimed to explore the potential role of LncRNA NEAT1 in AD. We found that LncRNA NEAT1 was up-regulated in the AD animal models. Furthermore, we demonstrated that NEAT1 could interact with NEDD4L and promote PINK1’s ubiquitination and degradation, then impaired PINK1 dependent autophagy. Collectively, the lncRNA NEAT1 promotes the pathogenesis of AD and serves as a promising novel target for pharmacological intervention.